Giant dielectric permittivity and high tunability in Y-doped SrTiO3 ceramics tailored by sintering atmosphere. (15th May 2017) - Tkach, Alexander; Okhay, Olena; Almeida, Abílio; Vilarinho, Paula M.
Abstract: Development of giant-permittivity and high-tunability dielectric materials has attracted great interest because of growing demand for smaller and faster energy-storage and electronic devices. Materials such as CaCu3 Ti4 O12, displaying the giant dielectric permittivity due to extrinsic Maxwell-Wagner interfacial polarization effect, have previously been reported. Ferroelectric materials possessing intrinsic ionic polarization due to a phase transition to the polar state have also been indicated to possess a high tunability of the dielectric permittivity by dc electric field. Here, a class of the giant-permittivity materials based on SrTiO3 ceramics doped with up to 1% of yttrium and their processing concept, which yields the dielectric permittivity up to ∼209, 000 at 10 kHz for nitrogen sintering atmosphere, and the relative tunability up to ∼74% under 20 kV cm −1 for oxygen sintering atmosphere, is reported. The high tunability is proved to be due to polar clusters created at low temperatures by off-central Y 3+ ions on Sr 2+ sites. The giant permittivity is explained by a coupling of the polar clusters relaxation mode with the donor substitution induced electrons at low temperatures and by the Maxwell-Wagner relaxation around room temperature. Besides the fundamental understanding, this discovery opens a new development window for high-frequency and low-temperature electronic and energy-storage applications. Graphical abstract: Image 1